Schismes avec le réel et autres névroses : discussion de l’ouvrage « Gouverner le climat ?» de Stefan Aykut et Amy Dahan - Jean Foyer (VertigO)
In their work of reference about climate change governance, Stefan Aykut and Amy Dahan propose the concept of « schism with reality » to describe series of gaps between this governance and different scientific, geopolitical and temporal realities. We come back to this central theory that we discuss threw three main points: the links between governance and governability, rationality in and between science and politics, and conflict of temporality. Finally, we give some news of the schism after COP21.